Gamifying Movement: A Comprehensive Survey of Physical Activity Interventions. - FATIMA, Shabih (Studies in Health Technology & Informatics, 2025)
Gamification has emerged as a powerful strategy for enhancing physical activity (PA) engagement by integrating motivational techniques and game elements into interventions. This research presents a comprehensive survey of gamified PA interventions by systematically analyzing the frequency of specific gamification elements and motivational techniques across various journal articles. A total of six major academic databases were examined to identify trends and research gaps in gamified PA applications. The study introduces the EAM Score Algorithm, which quantifies the presence and pairing of key game elements (e.g., leaderboard, challenges, progress bars) with motivational techniques (e.g., goal-setting, feedback, social support) to assess their impact on engagement, adherence, and motivation. To validate the EAM Score Algorithm, the study also analyzes 20 physical activity applications, including some of the most frequently studied PA apps. By comparing the frequency of gamification elements and motivational techniques in these apps with those in research articles, the study assesses the alignment between theoretical trends and real-world implementations. This approach helps identify gaps between academic research and practical application, providing valuable insights for researchers, health professionals, and developers working on gamified PA interventions. Findings indicate that engagement techniques (48.3%) are the most frequently discussed in the literature, highlighting their importance in gamified PA applications. Adherence (24.5%) is also a key focus but appears slightly less frequently. The overall EAM Score reflects a moderate emphasis on engagement, adherence, and motivation, indicating the need for a more balanced approach in future interventions. Using the EAM Algorithm, this research applies the framework in a real-world scenario by selecting the three most commonly studied apps. This implementation aims to evaluate the effectiveness of engagement, adherence, and motivation within these applications, providing insights into how gamification elements and motivational techniques influence user behavior. 52% of behavioral change techniques (BCTs) were identified in journal articles, making them the most frequently discussed motivational strategies compared to other techniques. The findings suggest that Health4Life offers the most well-balanced combination of engagement (68.35%), adherence (20.25%), and motivation (11.39%). Meanwhile, PuzzleWalk could strengthen its adherence strategies (12.50%) to enhance user adherence, while OnTheMove! may benefit from further improvements in its motivational components (11.48%) to sustain long-term engagement.